Color image analysis and machine learning for classification and flavonoid-equivalent prediction of Citri Reticulatae Pericarpium - Chuansen Qin; Huan Lu; Yichen Jia; Shuisheng Cao; Hongyan Wang; Haixiang Wang (Analytica Chimica Acta, 2026)

Applications of AI-assisted interpreter Raman spectroscopy platform for rapid and accurate cefotaxime-resistant Escherichia coli classification - Chenming Lu; Weifeng Zhang; Zhenfeng Zhao; Yichen Wang; Yuxuan Hu; Xiaolong Zhao; Zhanfang Zhao; Yirui Huang; Bo Zheng; Jingna Sun; Weili Hong; Pu Wang; et al. (Analytica Chimica Acta, 2026)

Functional Validation of the Phase I–II–III Detoxification Pathway in Azumapecten farreri using Optimized RNA Interference Technology - Limin Lu; Guanchao Zheng; Yichen Lin; Chenfan Dong; Jixing Peng; Haiyan Wu; Zhijun Tan (Marine Biotechnology, 2026)

City function matters: Identifying influential factors of urban thermal comfort - Lu Zhang; Yihao Cao; Chunhong Zhao; Shuang Wei; Yichen Wang; Pengyuan Liu (Computers, Environment and Urban Systems, 2026)

Corrigendum to “Collaboratively optimize of multi-scale spatial form within urban blocks for low-carbon performance: A machine learning-driven design support framework” [Sustainable Cities and Society, 143 (2026), 107342] - Gaomei Li; Hongxin Guo; Jian Kang; Yichen Dong; Hua Zhong; Anting Gao; Wei Lu; Shen Xu (Sustainable Cities and Society, 2026)

Silica nanoparticles disrupt blood–testis barrier integrity in Sertoli cells by inducing inflammation-mediated p38 MAPK pathway - Ying Wang; Wenpeng Liu; Yichen Wang; Dan Chen; Shoufang Jiang; Jinlong Li; Wenxuan Tang; Ping Lu; Xuan Shang (Reproductive Toxicology, 2026)

Evolution of PM2.5 chemical composition during summer new particle formation in a coastal city in the yangtze river delta: insights from pollution episodes, machine learning, and air mass origins - Han Zhou; Yichen Lu; Zeyi Li; Honglei Wang; Lijuan Shen; Yue Chen; Deyu Liu; Da Xu (Environmental Research, 2026)

Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

Soil microbial communities and reactive oxygen species reshape MAOC-driven PAH accumulation under seasonal trade-offs between forest filtering and cold trapping - Weijie Liu; Xinli Xing; Ying Liu; Andrew J. Sweetman; Kevin C. Jones; Shizhen Zhao; Yanqi Ma; Yichen Lu; Qinglong Fu; Tianpeng Hu; Jiaquan Zhang; Shihua Qi (Journal of Hazardous Materials, 2026)

Qualification rates and post-treatment spring regrowth reveal divergent efficacy of ten Spartina alterniflora control methods: evidence from 848 field-managed patches - Wanxia Yang; Yichen Cui; Yuting Cen; Yi Liu; Xiaoqiang Lu (Journal of Environmental Management, 2026)

Gut Microbiota Divergence Drives Aeromonas Hydrophila Resistance in Common Carp (Cyprinus carpio): Probiotic Role of Cetobacterium - Haidong Ma; Sitian Cheng; Yichen Zheng; Jia Cheng; Hongzhao Lu (Probiotics and Antimicrobial Proteins, 2026)

Rigid-flexible coupling errors calibration based on machine learning for robotic harvesting arm in orchard - Yichen Qiao; Qingchun Feng; Liping Chen; Congju Shen; Wenqiao Lu; Yajun Li; Yuhang Ma; Hongwen Li (Computers and Electronics in Agriculture, 2026)

Collaboratively optimize of multi-scale spatial form within urban blocks for low-carbon performance: A machine learning-driven design support framework - Gaomei Li; Hongxin Guo; Jian Kang; Yichen Dong; Hua Zhong; Anting Gao; Wei Lu; Shen Xu (Sustainable Cities and Society, 2026)

The G143S substitution of cytochrome b confers field resistance to pyraclostrobin in Glomerella cingulata - Xushi Jiang; Qian Yang; Yibo Man; Yichen Ma; Yujie Lu; Na Liu; Caixia Wang; Sen Lian; Baohua Li; Weichao Ren (Pesticide Biochemistry and Physiology, 2026)

Preparation of valuable furil catalyzed by flower-like ternary metal oxides under mild conditions - Zhenwei Yuan; Kun Yuan; Yichen Zou; Jian Kang; Dan Hou; Jianping Huang; Jing Chen; Lu He; Hualin Jiang; Wanming Xiong (Journal of Environmental Chemical Engineering, 2026)

High-Efficient synthesis of coal-based few-layer graphene by laser-induced: Regulation mechanism of coal maceral groups - Xiao Ma; Shaoqing Wang; Jingzhe Zhang; Yichen Mi; Xinyuan Song; Shanshan Lu; Xiaoguang Li (Fuel, 2026)

Isolation, characterization and biotechnological potential of a contaminant-derived cyanobacterium Sodalinema sp. ZYS - Yang Zhao; Zhichao Zhang; Yue Qiao; Yichen Li; Xiang Liu; Yan Liu; Tao Zhu; Xuefeng Lu (Bioresource Technology, 2026)

Scavenging multiple reactive carbonyl species simultaneously by mangiferin and its aglycone norathyriol in vitro and in vivo - Ruoying Du; Xiaoyun Jiang; Yichen Wang; Jin Wang; Bo Si; Chun Chang; Yonglin Lu; Lishuang Lv (Food Research International, 2026)

Vehicle-induced bridge dynamic response monitoring and displacement estimation using distributed acoustic sensing - Yichen Zhong; Chen Gu; Peng Wu; Zhanxiong Ma; Zhi Yuan; Zhuoyu Chen; Jiawei He; Chenrui Fan; Jiahui Wang; Dikai Wang; Xinzheng Lu (Engineering Structures, 2026)

Nudge waste out: Understanding the impacts of green nudges on on-site construction waste management based on metaverse serious game - Yaoliang Zhuang; Weisheng Lu; Ziyu Peng; Zhikang Bao; Liang Yuan; Yichen Yin (Environmental Impact Assessment Review, 2026)

Skin-triggered Janus physical cooling patches for prolonged evaporative cooling and superior comfort - Junyi Lu; Fuzhou Niu; Tonghuan Zhan; Heng Wang; Haojun Luo; Yichen Tang; He Wang; Xiaohua Yu; Weijie Zhang; Hao Chen; Bing Xu (Chemical Engineering Journal, 2026)

Emission reduction optimization of recycling pathways for retired photovoltaic modules in China: A coupled model of life cycle assessment and evolutionary game theory - Xu Zhu; Yichen Li; Yue Zhang; Yuanyuan Sun; Wen Xu; Lu Bai (Journal of Cleaner Production, 2026)

Metabolomics mechanisms of mulching and microbial fertilization in regulating horizon soil microbiomes of saline-alkali potato - Shujuan Jiao; Yong Wang; Yushan Wang; Xingxing Wang; Yuan Lu; Weina Zhang; Yuhui Liu; Shuhao Qin; Yichen Kang (Journal of Environmental Management, 2026)

Range-wide phenotypic variation in fruit and seed traits of Cyclocarya Paliurus across environmental gradients in China - Wanxia Yang; Yuting Cen; Yichen Cui; Xiaoqiang Lu; Shengzuo Fang (Plant Ecology, 2026)

Integrative Assessment of Interrelated Swimming Performances and their Physiological Basis in Large Yellow Croaker (Larimichthys crocea) - Wei Liu; Junjia Zeng; Jiaxing Liu; Tingsen Jiang; Yacheng Deng; Pengxin Jiang; Yin Li; Ningyuan Ding; Yichen Li; Yujia Chen; Chuan Deng; Haojie Li; et al. (Marine Biotechnology, 2026)

A meta-heuristic assisted path planning method for unmanned underwater vehicles and experimental validation - Jinsi Cai; Haiyan Xiao; Yichen Li; Guanghua Li; Dongdong Hou; Bingju Lu (Ocean Engineering, 2025)

Nonlinear responses of dryland vegetation GPP to climate and human drivers along aridity gradients in China and Mongolia - Haitao Zhang; Yifan Lu; Peng Tian; Yichen Yan; Ruoyu Wang; Shengnan Zhang; Weifeng Wang; Eerdun Hasi; Yingjun Xu (Journal of Environmental Management, 2025)

Biomimetic confined synthesis of copper-enriched polydopamine single-atom catalyst for synergistic catalysis of ammonium perchlorate and ammonium dinitramide decomposition - Wenqi Zhu; Chong Chen; Hongfeng Ji; Yong Kou; Yanchen Wang; Yichen Li; Qiangqiang Lu; Jun Di; Guigao Liu; Wei Jiang; Lei Xiao; Gazi Hao (Chemical Engineering Journal, 2025)

Integrating Landsat and MODIS data to assess long-term inundation patterns and vegetation response in wetland ecosystems - Dongshuo Lu; Xin’er Ning; Yichen Zheng; Hang Xiao; Xueli Wan; Jianbo Chang (Journal of Hydrology, 2025)

Quantifying human impacts on surface water dynamics via a convolutional LSTM approach - Dongshuo Lu; Lei Cheng; Xiaoning Liu; Yichen Zheng; Haobo Zhang; Jianbo Chang (Journal of Hydrology, 2025)

Unraveling hiatuses in black shales: Mechanisms and implications from the Lower Silurian Longmaxi Formation, South China - Yichen Liu; Benzhong Xian; Qianran Wu; Zhiyong Lu; Haocheng Shi; Mingjin Wu; Zhiyun Yu; Lin Zhao; Junyang Geng; Haiying Chen (International Journal of Coal Geology, 2025)

Phosphorylation of a conserved TBXT threonine residue is vital to vertebral development - Shuxia Chen; Chennan Liu; Ying Zhao; Lingbo Wang; Rui Peng; Lei Lu; Qian Yu; Yichen Jin; Jinsong Li; Xueyan Yang; Yunping Lei; Hongyan Wang (Science China Life Sciences, 2025)

Determination of 99Tc in TBP phase in spent nuclear fuel reprocessing with plastic scintillation resin - Man Wang; Tianyi Jia; Yiman Lu; Chenyang Peng; Hao Wang; Yichen Hu; Feng Zhang; Shan Xing; Keliang Shi; Weichao Zhang; Xiaolin Hou (Analytica Chimica Acta, 2025)

Cobalt-based nano-MOF additive to aluminum for enhancing energy release of energetic components - Chong Chen; Wenqi Zhu; Yanchen Wang; Jin Zhu; Qiangqiang Lu; Yichen Li; Lei Xiao; Jun Di; Guigao Liu; Wei Jiang; Gazi Hao (Chemical Engineering Journal, 2025)

Early-life indoor environmental exposures and COVID-19 outcomes in Chinese preschool children: A secondary analysis of a multicenter study - Chan Lu; Jing Ma; Zipeng Qiao; Yichen Yu; Wanxue Xu; Wewei Liu; Faming Wang (Journal of Hazardous Materials, 2025)

A study of the neurophysiological effects of peppermint odor on human thermal comfort - Songtao Hu; Yang Yang; Mingli Lu; Yichen Liu; Silin Zheng; Hongyu Guan; Li Tong (Building and Environment, 2025)

Metagenomics reveals an increased proportion of an Escherichia coli-dominated enterotype in elderly Chinese people - Jinyou Li; Yue Wu; Yichen Yang; Lufang Chen; Caihong He; Shixian Zhou; Shunmei Huang; Xia Zhang; Yuming Wang; Qifeng Gui; Haifeng Lu; Qin Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Statistical and theoretical analysis of iodine spiking phenomena during steam generator tube rupture - Changdong Lu; Yichen Chen; Zhijun Li; Pingting Jiang; Chao Yu; Pengtao Fu (Annals of Nuclear Energy, 2025)

Assessment of ecological risks and spatiotemporal monitoring of heavy metal contamination in cultivated soils of the Liaohe River Basin, Jilin Province, China - Yanan Chen; Jie Wang; Dianqi Pan; Yichen Zhang; Jiquan Zhang; Feng Zhang; Zengkang Lu (Science of The Total Environment, 2025)

Association between air pollution and hospitalization for acute exacerbation of kidney failure: A nationwide time-stratified case-crossover study in China - Yalan Xiao; Cong Liu; Yichen Liu; Huihuan Luo; Yixiang Zhu; Lu Zhou; Ya Gao; Hongliang Zhang; Renjie Chen; Jianwei Xuan; Haidong Kan (Journal of Hazardous Materials, 2025)

Evaluating climate change impacts on building level steady-state and dynamic outdoor thermal comfort - Jiwei Zou; Yichen Yu; Mohammad Mortezazadeh; Henry Lu; Abhishek Gaur; Liangzhu Wang (Building and Environment, 2025)

Three-way crossed scallops between Argopecten irradians irradians, A. i. concentricus and A. purpuratus exhibit strong heterosis in growth, survival and temperature tolerance - Jinjing Wang; Oscar Yichen Liu; Min Shen; Guilong Liu; Yinchu Wang; Xia Lu; Xin Xu; Quanchao Wang; Chunde Wang; Junhao Ning (Aquaculture, 2025)

Use of the diffusive gradients in thin-films (DGT) technique for smart rapid biomonitoring of trace metals in aquaculture systems - Runmei Wang; Jian Lu; Jun Wu; Yichen Lin; Feng Li; Cui Zhang; Jianhua Wang; Yingmin Zhou; Xiupeng Yue (Marine Environmental Research, 2025)

SARS-CoV-2 Inhibits Exo-Endocytosis and Enhances Short-Term Depression at a Central Synapse - Jiawei Hu; Yuhan Zhang; Qingzhuo Liu; Jiaqi Hu; Yichen Ru; Lu Zhang; Lixin Xie; Lei Xue (Neuroscience Bulletin, 2025)

Spatiotemporal variations of farmland crop residue burning in China from 2013 to 2022 - Lu Dong; Xin Long; Ziyi Wang; Meiying Xie; Xiao Han; Junji Cao; Zhanfeng Dong; Jinxin Yang; Yichen Wang (Science of The Total Environment, 2024)

Spaceborne high-spectral-resolution lidar ACDL/DQ-1 measurements of the particulate backscatter coefficient in the global ocean - Yichen Yang; Yudi Zhou; Iwona S. Stachlewska; Yongxiang Hu; Xiaomei Lu; Weibiao Chen; Jiqiao Liu; Wenbo Sun; Suhui Yang; Yuting Tao; Lei Lin; Weige Lv; et al. (Remote Sensing of Environment, 2024)

Rapid and accurate bacteria identification through deep-learning-based two-dimensional Raman spectroscopy - Yichen Liu; Yisheng Gao; Rui Niu; Zunyue Zhang; Guo-Wei Lu; Haofeng Hu; Tiegen Liu; Zhenzhou Cheng (Analytica Chimica Acta, 2024)

Dynamic response analysis of a fully coupled aerodynamic-hydrodynamic-mooring-anchor floating offshore wind turbine - Dongsheng Qiao; Yichen Zhou; Binbin Xu; Jianmin Qin; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean Engineering, 2024)

Unveiling the role of Cs ion in perovskite phase formation during solid–vapor reactions - Shenghan Hu; Peiran Hou; Changyu Duan; Shuang Zeng; Yichen Dou; Xinyu Deng; Yuxi Zhang; Jianfeng Lu; Yi-Bing Cheng; Yong Peng; Zhiliang Ku (Chemical Engineering Journal, 2024)

Research on Model Reduction of AUV Underwater Support Platform Based on Digital Twin - Daohua Lu; Yichen Ning; Jia Wang; Kaijie Du; Cancan Song (Journal of Marine Science and Engineering, 2024)
Digital twin technology, as a data-driven and model-driven innovation means, plays a crucial role in the process of digital transformation and intelligent upgrading of the marine industry, helping the industry to move towards a new stage of more intelligent and efficient development. In order to solve the defects of the Autonomous Underwater Vehicle (AUV) underwater support platform structure deformation field, digital twin technology and model reduction technology are applied to an AUV underwater support platform, and a five-dimensional digital twin model of the AUV underwater support platform is studied, including five dimensions: physical world, digital world, twin data center, service application, and data connection. The digital twin of the subsea support platform is established by using the digital twin modeling technology. The POD method is used to calculate the deformation field matrix of the support structure of the subsea support platform under the 0–5 sea state, and the corresponding eigenvalues and eigenvectors are obtained. By intercepting the eigenvectors corresponding to the eigenvalues of the high energy proportion, the low-order equation is constructed, and the reduced-order model under each sea state can be quickly solved. The experimental results show that the model reduction technology can greatly shorten the model solving time, and the calculated results are highly consistent with the simulation results of the finite element full-order model, which can realize the rapid analysis of the deformation response of the subsea support platform structure, and provide a theoretical basis and technical support for the subsequent simulation, state evaluation, visual monitoring, and predictive maintenance.

The greener the living environment, the better the health? Examining the effects of multiple green exposure metrics on physical activity and health among young students - Yuheng Mao; Tianyu Xia; Fan Hu; Dan Chen; Yichen He; Xing Bi; Yangcen Zhang; Lu Cao; Jingheng Yan; Jinyu Hu; Yanzi Ren; Hongmei Xu; et al. (Environmental Research, 2024)

Ecological responses to hydrological connectivity in grassland riparian zones: Insights from vegetation and ground-dwelling arthropods - Mengmeng Ye; Haizhu Hu; Panlong Wu; Zhengyu Xie; Yichen Hu; Xixi Lu (Science of The Total Environment, 2024)

Short-term high temperature may increase the incidence risk of collective conflicts: A case-crossover study in the Greater Middle East - Yichen Guo; Ya Gao; Cheng He; Yixiang Zhu; Lu Zhou; Haidong Kan; Renjie Chen (Science of The Total Environment, 2024)

Ultrafast and selective capture of 99TcO4-/ReO4- from wastewater by hyper-branched quaternary ammonium group-functionalized resin - Juan Tong; Junqiang Yang; Xiaobo Li; Kesheng Hu; Yiman Lu; Man Wang; Yichen Hu; Keliang Shi (Journal of Hazardous Materials, 2024)

Cellular and Molecular Roles of Immune Cells in the Gut-Brain Axis in Migraine - Yichen Zhou; Miaoyi Pang; Yiran Ma; Lingling Lu; Jiannan Zhang; Peipei Wang; Qian Li; Fei Yang (Molecular Neurobiology, 2024)

Influences of intraseasonal oscillations on a compound cold and wet event in southern China during the Spring Festival travel rush - Lu Chuhan; Shen Yichen; Wang Yihan; Xin Fei (International Journal of Climatology, 2024)
In January 2023 during the Spring Festival travel rush, a compound cold and wet event (CCWE) hit southern China, causing heavy precipitation followed by two cold wave processes. Through an analysis from the intraseasonal oscillation (ISO) perspective, it was found that the cold event is caused by two consecutive cold events, in which upper level midlatitude ISO wave train propagating across the Eurasia favours the formation of blocking high, leading to the expansion of Siberian High and intensification of East Asian winter monsoon. As a result, strong cold advection appeared in the northern boundary of southern China and caused the cooling process. As for the wet event, it was found that a cyclonic ISO anomaly from South China Sea conveyed abundant moisture through the western and southern boundaries and caused the precipitation. It was revealed in the partial lateral forcing (PLF) experiment that the midlatitude ISO signal from the northern boundary caused minimum 2 m temperature to drop by 1.84°C, mainly affecting the northern part of the research area. The tropical ISO from the western and southern boundaries resulted in heavy precipitation for over 40 mm in a belt‐shaped area in 3 days. The combination of the ISOs is the key factor behind this CCWE and our study provides intuitive evidences for this, which is helpful in understanding the mechanisms and providing empirical precursory signals for the forecast of CCWEs.

Long-term spatiotemporal variations in surface NO2 for Beijing reconstructed from surface data and satellite retrievals - Zixiang Zhao; Yichen Lu; Yu Zhan; Yuan Cheng; Fumo Yang; Jeffrey R. Brook; Kebin He (Science of The Total Environment, 2023)

Source and health risk assessment of soil polycyclic aromatic hydrocarbons under straw burning condition in Changchun City, China - Jie Wang; Yanan Chen; Dianqi Pan; Jiquan Zhang; Yichen Zhang; Zengkang Lu (Science of The Total Environment, 2023)

Acaricidal and repellent activities of ethanol extracts of nine chinese medicinal herbs against Rhipicephalus microplus (Acari: Ixodidae) - Donglinag Li; Shunli Lu; Yichen Jian; Shuqi Cheng; Qianming Zhao; Huizhen Yuan; Nanhao Wang; Yufeng Liu; Sumei Zhang; Longxian Zhang; Rongjun Wang; Fuchun Jian (Experimental and Applied Acarology, 2023)
Rhipicephalus microplus is a major threat to the cattle industry worldwide. The intensive use of acaricides and repellents has resulted in drug resistance. Hence, effective and eco-friendly pest control alternatives are urgently needed, especially from natural plant resources. In this study, the acaricidal and repellent activities of nine herbs against the larvae and eggs of R. microplus were evaluated. The results showed that ethanol extracts of star anise ( Illicium verum ), chaulmoogra ( Hydnocarpus anthelmintica ), motherwart ( Leonurus artemisia ), mandarin orange peel (citri reticulatae pericarpium, i.e., peel of Citrus reticulata fruit), and stemona ( Stemona sessilifolia ) had good contact acaricidal activities of 100, 98, 94, 88 and 86%, respectively, whereas star anise and clove ( Syzygium aromaticum ) had good fumigant acaricidal activities of 98 and 96%, respectively. The hatching inhibition rate of star anise against R. microplus eggs was 100%. All nine herbs had good real-time repellent rates, but only castor bean and star anise had repellent effects after 48 h (81.3 and 79.6%, respectively). This is the first report of the acaricidal and repellent activities of these medicinal herbs against R. microplus . Ethanol extracts of these herbs might be considered as potential alternatives to chemical acaricides for control of R . microplus .

In-situ synthesis of floating ZnIn2S4/cellulose foam for facile photocatalysis - Yichen Zhou; Ying Zhang; Lu Zhang; Jianhao Qiu; Jianfeng Yao (Carbohydrate Polymers, 2023)

Spatiotemporal variations in meteorological influences on ambient ozone in China: A machine learning approach - Tao Li; Yichen Lu; Xunfei Deng; Yu Zhan (Atmospheric Pollution Research, 2023)

Microplastic pollution destabilized the osmoregulatory metabolism but did not affect intestinal microbial biodiversity of earthworms in soil - Ronggui Tang; Minshen Ying; Yongming Luo; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Tao Sun; Yutao Cao; Zhihan Diao; Yuxin Zhang; Yichen Lian; Keyi Chen; Yan Yan; et al. (Environmental Pollution, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Role of Intraseasonal Oscillation in a Compound Drought and Heat Event over the Middle of the Yangtze River Basin during Midsummer 2018 - Chuhan Lu; Yichen Shen; Yonghua Li; Bo Xiang; Yujing Qin (Journal of Meteorological Research, 2022)

Altered microstructural properties of superficial white matter in patients with Parkinson’s disease - Yichen Zhang; Biao Huang; Qinyuan Chen; Lijuan Wang; Lu Zhang; Kun Nie; Qinda Huang; Ruiwang Huang (Brain Imaging and Behavior, 2022)

Continental-scale spatial distribution, sources, and health risks of heavy metals in seafood: challenge for the water-food-energy nexus sustainability in coastal regions? - Jian Lu; Yichen Lin; Jun Wu; Cui Zhang (Environmental Science and Pollution Research, 2021)

Severe Nitrate Pollution and Health Risks of Coastal Aquifer Simultaneously Influenced by Saltwater Intrusion and Intensive Anthropogenic Activities - Jun Wu; Jian Lu; Xiaohu Wen; Zhenhua Zhang; Yichen Lin (Archives of Environmental Contamination and Toxicology, 2019)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Detected microsatellite polymorphisms in genetically altered inbred mouse strains - Xiaoyan Du; Jing Cui; Chao Wang; Xueyun Huo; Jing Lu; Yichen Li; Zhenwen Chen (Molecular Genetics and Genomics, 2013)